Charging toward decarbonized electrification: Revisiting Beijing's power system - Da Huo; Qian Zhang; Yujie Dong; Christopher Kennedy; Chao Zhang (Energy Strategy Reviews, 2023)
Beijing's power system has experienced a significant transition by eliminating coal-fired power generation and increasing the extent of electrification over the past two decades. This study uses a plant-level dataset, pair-wise energy flow, and customized index decomposition analysis to investigate the driving forces behind Beijing's rapid electrification and carbon mitigation effects. Our assessment approaches can reveal the role of electrification in driving city-level emissions and identify a reasonable timeline to accelerate electrification for cities. We find that electrification-related factors are responsible for 21.8% of carbon emission changes in Beijing between 1995 and 2019. The extent of electrification in Beijing has doubled from 9.5% in 1995 to 19% in 2019, while the carbon intensity of electricity consumption has reduced by 26%. Particularly, the average emission intensity of Beijing's local power generation has dropped from 860 tCO2e/GWh in 2000 to 370 tCO2e/GWh in 2018, which is far below a critical level at which the high penetration of electricity in transportation and housing should be prioritized for decarbonization. Our results confirm that Beijing is in the best position to accelerate electrification to meet its carbon neutrality goals; however, this will increasingly rely on regionally collaborative decarbonization efforts with surrounding regions.